VD_FINDINFO Arrêt / 2018 / 215 vom 15. März 2018 - VD Tribunal cantonal (2018)
GAIN ASSURÉ, HEURES DE TRAVAIL SUPPLÉMENTAIRES | 321c al. 3 CO, 23 al. 1 LACI, 9 al. 1 let. a LTr, 37 al. 1 OACI, 37 al. 2 OACI